Biomassa e dinâmica de nutrientes em leguminosas, em resposta à adubação nitrogenada e à inoculação com Rhizobium - Mangaravite, José Carlos Soares (2011)
Green manuring is recognized as a viable alternative in the pursuit of sustainability of agricultural soils. Legumes have been preferred for green manuring for associating the symbiotic diazotrophic bacteria to fix atmospheric nitrogen. The root system of